Effect of Routine dental procedures on the pulse rate and peripheral oxygen saturation in pediatric patients - Khanal, Sanskriti; Shah, Priyanka; Khapung, Anju (Nepal Medical College Journal, 2023)
Dental treatment can cause anxiety in a child further leading to physiological changes that affects the success of dental care. This cross-sectional study was carried out to assess the changes in the pulse rate and peripheral oxygen saturation in children undergoing routine dental treatment. Total 80 patients of 6 to 12 years old were included in the study who were divided into four groups according the dental treatment they receive. Data was analyzed using SPSS-16. It was observed that the patients undergoing extraction (group IV) had higher mean pulse rate before, during and after the procedures; 100.25±9.33, 101.85±13.52, 98.85±7.63 respectively. Lowest SpO2 was recorded in the patients undergoing pulp therapy before the procedure (96.90±3.66). Pulse rate was higher in females compared to males but it was not statistically significant. The children in extraction group selecting facial image scale 4 had more mean pulse rate before during and after the procedure. The mean pulse rate was high in patients undergoing extraction in both first visit (103.00±9.21) and subsequent visits (101.36±15.28). It was concluded that physiological changes occur during routine dental treatment therefore monitoring should be done in order to prevent any dental emergencies.